2011
DOI: 10.1097/pcc.0b013e3182192c96
|View full text |Cite
|
Sign up to set email alerts
|

16q24.1 microdeletion in a premature newborn: Usefulness of array-based comparative genomic hybridization in persistent pulmonary hypertension of the newborn

Abstract: Objective Report of a 16q24.1 deletion in a premature newborn, demonstrating the usefulness of array-CGH in persistent pulmonary hypertension of the newborn (PPHN) and multiple congenital malformations. Design Descriptive case report Setting Genetic department and neonatal intensive care unit of a tertiary care children’s hospital Patient We report the case of a preterm male infant, born at 26 weeks of gestation. A cardiac malformation and bilateral hydronephrosis were diagnosed at 19 weeks of gestation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Approximately one-third of cases also have associated pulmonary lymphangiectasia (13). Mutations or deletions in Forkhead box F1 (FOXF1) have been found in up to 40% of infants with ACD-MPV, and there is a high (up to 80%) association with cardiac, gastrointestinal, and genitourinary anomalies (14)(15)(16).…”
Section: Child Entities More Prevalent In Infancy Diffuse Developmentmentioning
confidence: 99%
“…Approximately one-third of cases also have associated pulmonary lymphangiectasia (13). Mutations or deletions in Forkhead box F1 (FOXF1) have been found in up to 40% of infants with ACD-MPV, and there is a high (up to 80%) association with cardiac, gastrointestinal, and genitourinary anomalies (14)(15)(16).…”
Section: Child Entities More Prevalent In Infancy Diffuse Developmentmentioning
confidence: 99%
“…This recommendation is based upon the observation that up to 40% of newborns with hypoxemia and severe pulmonary hypertension due to ACD-MPV have FOXF1 deletions or mutations, according to two case reports (165,166) and a case series (107). The recommendation reflects our judgment that the benefits of identifying patients with such mutations (i.e., avoiding the risks and burdens of surgical lung biopsy, patient and family preferences) exceed the cost of genetic testing (Table E1).…”
Section: Age-specific Considerations: Newborns With Severe Child Syndmentioning
confidence: 99%
“…10,11 The craniofacial dysmorphism seen in our patient was most likely due to the larger microdeletion disorder, but the primary phenotype can be ascribed to the deletion of the FOX gene cluster (FOXF1,FOXC & FOXL) as there are multiple similarities between our patient and those described by Stankiewicz et al, who reported ACD caused by the loss of function of FOXF1. 7,[12][13][14] ACD should be considered in neonates of any gestational age presenting with pulmonary hypertension or hypoxemic respiratory failure, especially if associated with cardiovascular or gastrointestinal anomalies or mutations of the FOX gene cluster. Our description of bronchial abnormalities in association with ACD, as well as the documented association between ACD and subglottic stenosis by Shimizu et al, suggest that ACD should be a diagnostic consideration in neonates with pulmonary hypertension and/or hypoxemic respiratory failure and proximal airway anomalies.…”
Section: Discussionmentioning
confidence: 99%